The Meanings of Sentence Insistence in Karo Language - Efendi Barus (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
The aims of writing this research are to analyze about the use of particles in language and also the shift of words from one position to another one and they become what are called sentence insistence or sentence emphasis in Karo Language. The method of this research is by using descriptive research or library research. The analysis elaborates all types of insistence that can give effect to the meanings of the sentences which can be divided into 5 (five) types, such as: word stress, clauses in contradiction, the use of passive voice and the shift of words from one place to another one. The conclusion of this research shows the aspects of discussion such the types of insistence and how the meanings are found or described.